Impact of physical activity, BMI and sociodemographic and lifestyle factors on the risk of diabetes in 9,511 Ghanaian adults - López Sánchez, Guillermo Felipe; Vigueras Hernández , María Rosa; Lucas Casas , Pablo; Zauder, Roksana; Jastrzębska , Joanna; Skalska , Maria; Radzimiński , Lukasz; Jastrzębski , Zbigniew; Pardhan , Shahina (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to analyze the impact of physical activity, BMI, sociodemographic and life-style factors on the risk of diabetes in Ghana. We analyzed data from 9,511 Ghanaian adults that had participated in Waves 0 and 1 of the World Health Organization Study on Global Ageing and Adult Health. To assess diabetes participants were asked: “Have you ever been diagnosed with diabetes (high blood sugar)?”. The impact of nine exposure variables (physical activity, BMI, sex, age, marital status, education, smoking, alcohol intake, and fruit and vegetables consumption) on the risk of diabetes was analyzed with chi-square tests and multivariate regression analyses, separately in each wave to observe the evolution of diabetes risk factors in Ghana. In both adjusted and unadjusted analyses, the exposure characteristics significantly associated (p<0.05) with dia-betes were < 600 MET-minutes/week of physical activity (wave 1), obesity (wave 0), female sex (wave 1), age ≥ 60 years (waves 0 and 1) and education (wave 1). Therefore, these factors should be taken into account to develop public health strategies to reduce diabetes in Ghana. Considering the results of this study, an adequate strategy might be the implementation of physical education programs in people with obesity, women and older adults from Ghana.